Activation of cellular apoptosis in the caecal epithelium is associated with increased oxidative reactions in lactating goats after feeding a high‐concentrate diet. Issue 3 (12th February 2015) - Tao, Shiyu; Tian, Jing; Cong, Rihua; Sun, Lili; Duanmu, Yongqian; Dong, Haibo; Ni, Yingdong; Zhao, Ruqian
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? What are the ultrastructural changes of the caecal mucosa and the status of epithelial cellular apoptosis and oxidative reactions in lactating goats after prolonged feeding with a high‐concentrate diet? What is the main finding and its importance? High‐concentrate diet results in ultrastructural damage to the caprine caecal epithelium. Increased oxidative and decreased antioxidative reactions are involved in the process of activating epithelial apoptosis in the caecal epithelium of goats fed a high‐concentrate diet. Our results provide new insight into the relationship between abnormal fermentation in the hindgut and damage to the intestinal mucosal barrier. The effect of feeding a high‐concentrate diet (HC) to lactating ruminants on their hindgut epithelial structure remains unknown. In this study, 12 lactating goats were randomly assigned to either HC (65% of dry matter as concentrate; n = 6) or a low‐concentrate diet (LC; 35% of dry matter as concentrate; n = 6). After 10 weeks, the epithelial ultrastructure and cell apoptotic status in the caecal mucosa were determined by transmission electron microscopy and TUNEL, respectively. The results showed that the level of free lipopolysaccharide (P < 0.05), total volatile fatty acid concentrations (P < 0.1) and starch content (P < 0.05) in the caecal digesta were significantly increased in HC‐ compared with LC‐fed goats. The HC‐fed goats exhibited obvious epithelial cellular damage, with widened tight junction spaces, nuclear breakdown and mitochondrial swelling. Compared with their LC‐fed counterparts, HC‐fed goats showed greater apoptosis in the caecal epithelium, as evidenced by more TUNEL‐positive apoptotic cells. Western blot analysis showed that there was no significant difference in activated caspase‐3, Bax protein expression in caecal epithelial mucosa between HC‐ and LC‐fed goats (P > 0.05). However, the level of malondialdehyde content in the caecal epithelium from HC‐fed goats was markedly higher than that in LC‐fed goats (P < 0.05), whereas the level of glutathione peroxidase and the superoxide dismutase activity were significantly decreased. Gene expressions of cytokines, including interleukin‐1β, interleukin‐6, interleukin‐10, tumour necrosis factor‐α and interferon‐γ, as well as myeloperoxidase activity in the caecal mucosa did not show any significant difference between HC‐ and LC‐fed goats. These results indicate that feeding a high‐concentrate diet to lactating goats for a prolonged period results in abnormal fermentation and structural disruption in the hindgut, which is accompanied by greater cellular apoptosis and an enhanced oxidative stress response.